2004
DOI: 10.1016/j.amjhyper.2004.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between changes in neck circumference and changes in blood pressure

Abstract: Changes in systolic BP and diastolic BP correlated positively with changes in NC and other components of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 24 publications
5
58
2
4
Order By: Relevance
“…Ben Noun et al, [9][10][11][12] observed relationship between changes in neck circumference and changes in blood pressure. They found that changes in systolic BP and diastolic BP correlated positively with changes in NC and other components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben Noun et al, [9][10][11][12] observed relationship between changes in neck circumference and changes in blood pressure. They found that changes in systolic BP and diastolic BP correlated positively with changes in NC and other components of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In a first cross sectional study by Ben-Noun et al, [9][10][11][12] which was done to identify overweight or obese patients solely by measuring the circumference of the neck, observed that NC >37cm for men and >34cm for women were the best cutoff levels for determining the subjects with BMI >25.0 kg/m 2 using the receiver output curve analysis. In our study we also observed same characteristics as NC 37 cm for men and 34 cm for women identified subjects with BMI >25.0 kg/m 2 with 75% to 86% sensitivity for men and 63% to 93% for women, 80% to 90% specificity for men and 80% to 100% for women.…”
Section: Discussionmentioning
confidence: 99%
“…Neck circumference (NC) has been proposed as a useful indicator to measure upper body obesity in different studies in the past [3,[14][15][16][17][18]. These studies have shown that men with NC < 37 cm and women with NC < 34 cm have a low body mass index [14].…”
Section: Discussionmentioning
confidence: 99%
“…[2] stated that the proportion classified as obese increased from 6 percent among men aged [15][16][17][18][19] to 33 percent of men aged 55-59. Urban men were much more likely than rural men to be obese (22 percent and 15 percent, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…NC was found to be related to the other anthropometric measures of obesity and fat distribution in many studies (17,18,28), which confirmed the results of Pearson correlation in the present study. Ben-Noun and Laor concluded that changes in NC were correlated with changes in CVD risk since it was correlated strongly with changes in SBP and DBP, and some other factors of the metabolic syndrome (17,29).…”
Section: Discussionmentioning
confidence: 99%